The Segment of the Newspapers for the Third Age – Specifics and Profiles of the Editions - Tsankova, Svetla (Research Papers, 2021)
Newspapers for the elderly people are amongst the few that have developed very successfully despite the serious crisis of the print media in Bulgaria in the last decade. The goal of this study is to look for both – the general trends of the segment as well as the specific characteristics of each and every edition and to derive the formula for good market positioning applied.Content analysis, analysis of the media surveys and statistics are used as the main methods. The results lead to the conclusion that each of the weekly magazines in the segment has found its specific concept and a few general models stand out – which will be present in this study. The analysis of the segment shows that the successful formula is: affordable cost for the consumers, balance between useful and interesting information and a loyal audience.The survey was conducted in the period June – July 2020, while the systematic monitoring of the segment dates from 2010 to present. This allows us to follow the process of its development and adaptation to the changes in the press in our country. Unfortunately, the good market positions of the weekly editions for elderly people are rarely the subject of research attention, nevertheless they could be a good model for the survival of the print media in Bulgaria.
Keywords: Firm strategy; Market performance; Weekly newspapers; Pensioners’ newspapers; Newspaper concept